2020
DOI: 10.1088/1742-6596/1516/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Improving self-efficacy in the teaching of prospective mathematics teachers by involving them in the online teacher community

Abstract: Self-efficacy in teaching is very important for prospective teachers. Prospective teachers who have good self-efficacy inteaching can carry out the profession as a teacher well in the future. This study aims to improve the self-efficacy in teaching of prospective mathematics teachers by involving them in the online teacher community. A total of 58 prospective mathematics teachers were included as samples. They were divided into two groups. The experimental group attended micro teaching courses while involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…According to our findings Greek in-service elementary school teachers improved their self-efficacy beliefs thus going in line with Aji and Khan (2019), Gosselin et al (2010), Mertasari andCandiasa (2020), andYoo (2016) who reported the same findings. However, our results do not comply with the findings of Wang and Zhu (2019) who reported no change in undergraduate chemistry students' self-efficacy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…According to our findings Greek in-service elementary school teachers improved their self-efficacy beliefs thus going in line with Aji and Khan (2019), Gosselin et al (2010), Mertasari andCandiasa (2020), andYoo (2016) who reported the same findings. However, our results do not comply with the findings of Wang and Zhu (2019) who reported no change in undergraduate chemistry students' self-efficacy.…”
Section: Discussionsupporting
confidence: 87%
“…They mainly investigate the enhancing teachers' professional development through issues of improvement, such as content knowledge, beliefs, and teaching practices of in-service and pre-service teachers, take place in different countries and use quantitative and qualitative approaches (Gordillo et al, 2019;Menon & Banerjee, 2019;Rahimi et al, 2018). Nevertheless, only a narrow range of studies have focused on the effectiveness of TPD-MOOCs (Gamage et 3 / 14 al., 2016;Reddy & Pabolu, 2019) and very limited studies investigate the MOOCs impact on teachers' selfefficacy beliefs (Aji & Khan, 2019;Gosselin et al, 2010;Mertasari & Candiasa, 2020;Wang & Zhu, 2019;Yoo, 2016). Specifically, Aji and Khan (2019) measured the self-efficacy beliefs of 16 math's and 18 science teachers in the USA, who participated in a workshop related with teaching math's and physics concepts to middle school students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the participants note the effort that the teacher makes influences the learning outcomes, students' achievements in biological concepts are related to teacher effectiveness but teachers cannot generally be blamed for the student's achievements. The above findings are consistent with the findings of Aji and Khan (2019), Gosselin et al (2010), Mertasari andCandiasa (2020), andYoo (2016), who argue that the improvement of teachers' self-efficacy in other fields and highlight the potential of online courses as a model of professional development of teachers.…”
Section: Discussionsupporting
confidence: 90%
“…Studies report improvement of teachers' self-efficacy they participate in professional development courses (Mulholland et al, 2004;Kreischer-Gajewicz, 2019), which over the last decade have increasingly been offered in the form of online distance learning courses (Aji & Khan, 2019;Mertasari & Candiasa, 2020;Yoo, 2016). These courses are facilitated by the digital revolution and enhance opportunities to teachers for utilization of technology platforms, mobile devices, social media, and access to digital educational content and OERs.…”
Section: Introductionmentioning
confidence: 99%